The influence of segmental errors and stress-placement errors on Polish listeners’ perceived degree of foreignaccentedness in non-native speech - Anna Borkowska (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
Polish listeners’ perception of different types of errors in non-native speech was studied with a focus on segmental and stress-placement errors. The stimuli consisted of the speech produced by Polish learners of Russian, Czech, and Spanish origins. The results which were obtained suggest that segmental errors (i.e., errors related to the pronunciation of segments) influence the foreignaccentedness perceived by Polish listeners significantly more than stress-placement errors. That is probably due to stress-deafness experienced by native speakers of Polish. While stress-placement errors resulted in relatively low scores in terms of foreignaccentedness, the ratings for segmental errors depended on the L1 group of the speakers. Segmental errors produced by speakers of Spanish were rated as the most foreign-sounding, followed by Czech and Russian. One possible explanation is that it was caused by the sound systems of Russian, Czech, and Polish being pretty similar, while the Spanish sound system is somewhat different.